Nanotechnological approaches in topical RNAi therapy for skin diseases - Ualisson José da Silva; Milena Finazzi Morais; João Vitor de Almeida Pereira; Maria Vitória Lopes Badra Bentley (Academia Biology)
The discovery of RNA interference (RNAi) has revolutionized molecular biology and therapeutic development, offering a novel approach to gene silencing. Despite significant progress, a critical gap remains in fully harnessing the potential of RNAi-based therapies for a broader range of diseases, particularly beyond hepatic targets. This review focuses on strategies to overcome the unique barriers posed by the skin and examines recent advances in nanoparticle-based delivery systems for RNAi therapies targeting skin diseases. Nanoparticles (NPs)—including lipid-based, inorganic, and polymer-based carriers—have demonstrated improved drug delivery, offering sustained release and precise therapeutic effects. Although several RNAi-based drugs have already been approved, further research is necessary to expand their application to skin diseases. Furthermore, innovative delivery systems are crucial for enhancing therapeutic efficacy, particularly in overcoming the skin barrier. The findings indicate that despite considerable progress, further innovation in NP design and delivery mechanisms is essential to fully exploit the potential of RNAi therapies in dermatology.